СИСТЕМА ВИДАТКІВ З ВОЛОСНИХ БЮДЖЕТІВ ЧЕРНІГІВСЬКОЇ ГУБЕРНІЇ І ПОЛ. ХІХ СТ. (Zaporizhzhia Historical Review, 2021)
System of expenditures from the district budgets on the local necessities of Chernihiv province in the first half of XIX century. Use new archival data that are leading into scientific circulation at first time. System of expenditures from the district budgets of Chernihiv province in the first half of XIX century.